2020
DOI: 10.1016/j.jaci.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

B lymphocytes directly contribute to tissue fibrosis in patients with IgG4-related disease

Abstract: Background: IgG 4-related disease (IgG 4-RD) is a fibroinflammatory condition marked by rapid clinical improvement after selective depletion of B lymphocytes with rituximab. This feature suggests that B cells might participate in fibrogenesis and wound healing. Objective: In the present work we aimed to demonstrate that B lymphocytes contribute directly to tissue fibrosis in patients with IgG 4-RD. Methods: Total circulating CD19 1 B lymphocytes, naive B cells, memory B cells, or plasmablasts from patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 68 publications
1
68
0
5
Order By: Relevance
“…The first inflammatory phase of IgG4-RD is characterized by the appearance of antigen experienced B and T lymphocytes that accumulate at disease sites, engage in mutual activating antigen driven interactions, and secrete pro-fibrotic molecules such as interleukin 1β, interleukin 6, interferon γ, transforming growth factor β, platelet derived growth factor B, and lysyl oxidase homologue 2 414243. These populations of activated lymphocytes include circulating plasmablasts, T effector memory (T EM ) cytotoxic T lymphocytes (CTLs), and CD45RA+TEM (T EMRA ) CTLs 3233343536.…”
Section: Overview Of Disease Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…The first inflammatory phase of IgG4-RD is characterized by the appearance of antigen experienced B and T lymphocytes that accumulate at disease sites, engage in mutual activating antigen driven interactions, and secrete pro-fibrotic molecules such as interleukin 1β, interleukin 6, interferon γ, transforming growth factor β, platelet derived growth factor B, and lysyl oxidase homologue 2 414243. These populations of activated lymphocytes include circulating plasmablasts, T effector memory (T EM ) cytotoxic T lymphocytes (CTLs), and CD45RA+TEM (T EMRA ) CTLs 3233343536.…”
Section: Overview Of Disease Pathophysiologymentioning
confidence: 99%
“…Both plasmablasts and effector memory T cells express the signaling lymphocytic activation molecule F7 (SLAMF7), a surface protein that has been implicated in cell-cell interaction and chronic lymphocyte activation 3233343536. Although involvement of T EM and T EMRA CTLs in tissue fibrosis has not been clearly demonstrated, plasmablasts/plasma cells from patients with IgG4-RD have been shown to prompt fibroblast activation and collagen production in vitro, thus partially explaining the improvement of fibrotic lesions with B cell depletion 34414243…”
Section: Overview Of Disease Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports have shown that LOXL2 is associated with various types of fibrotic diseases. 9 In the study by Della-Torre et al, 8 immunohistochemistry data demonstrated abundant LOXL2 expression in B cells infiltrating IgG 4 -RD tissue. Moreover, the intriguing finding is that plasmablasts from patients with IgG 4 -RD expressed type I collagen genes.…”
mentioning
confidence: 94%
“…In this issue of the Journal of Allergy and Clinical Immunology, Della-Torre et al 8 reported the direct contribution of B lymphocytes to tissue fibrosis in patients with IgG 4 -RD. Of note, they provided the first evidence that plasmablasts (which the authors focused on as a population with major involvement in IgG 4 -RD pathophysiology) represent a B-cell subset with intrinsic fibrogenic potential in IgG 4 -RD in contrast to both naive and memory B cells.…”
mentioning
confidence: 99%